2014
DOI: 10.1105/tpc.114.124867
|View full text |Cite
|
Sign up to set email alerts
|

A Zinc Finger Protein Regulates Flowering Time and Abiotic Stress Tolerance in Chrysanthemum by Modulating Gibberellin Biosynthesis    

Abstract: Flowering time and an ability to tolerate abiotic stresses are important for plant growth and development. We characterized BBX24, a zinc finger transcription factor gene, from Chrysanthemum morifolium and found it to be associated with both flowering time and stress tolerance. Transgenic lines with suppressed expression of Cm-BBX24 (Cm-BBX24-RNAi) flowered earlier than wild-type plants and showed decreased tolerance to freezing and drought stresses. Global expression analysis revealed that genes associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
158
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(161 citation statements)
references
References 72 publications
3
158
0
Order By: Relevance
“…As in our previous work we found that CmBBX24 acts as a negative regulator in phytochrome and light signaling (Yang et al 2014). In the present investigation we examined CmBBX24 promoter activity in response to white light, blue light, red light, far-red light, and monochromatic light.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…As in our previous work we found that CmBBX24 acts as a negative regulator in phytochrome and light signaling (Yang et al 2014). In the present investigation we examined CmBBX24 promoter activity in response to white light, blue light, red light, far-red light, and monochromatic light.…”
Section: Discussionmentioning
confidence: 78%
“…In our previous work, we isolated the full-length transcript of the BBX24 gene from young leaves of chrysanthemum and found that the gene plays an important role in abiotic stress tolerance and the flowering process in chrysanthemum (Yang et al 2014). In the present investigation, we studied the CmBBX24 promoter and found it to be very active, playing an important role in response to abiotic stress, hormones, and light treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implication is that the GA pathway regulates floral induction under LD, operating via CmFTL1 SOC1 and LFY. Previous report showed that the transcript level of CmFTL3 was up-regulated specifically by GA [33], which might be due to different genetic backgroud of cultivars.…”
Section: Ga Activates Cmftl and Soc1 To Promote Flowering Under Ldmentioning
confidence: 99%
“…It has also been established from the behavior of A. thaliana plants grown under SD that GA induces SOC1 transcription to promote flowering [12,32]. In chrysanthemum, the loss of BBX24 (a zinc finger transcription factor) not only accelerates flowering, but also induces the photoperiod and GA synthesis pathways [33]. Meanwhile, the transcription of catabolic gene GA2ox and GAI is inhibited in WT and M plants under SD.…”
Section: The Photoperiod and Ga Pathways Act In Concert To Regulate Fmentioning
confidence: 99%